(untitled) (Research, Society and Development, 2024)
Canine Cognitive Dysfunction Syndrome (CCDS) is a progressive neurodegenerative condition affecting elderly dogs, with neuropathological features similar to Alzheimer’s Disease (AD) in humans. CCDS is characterized by cerebral changes such as beta-amyloid plaque deposition, neurofibrillary tangles, and neuronal loss, leading to behavioral changes, including disorientation, sleep-wake cycle disturbances, and cognitive decline. Diagnosis is based on clinical signs and is facilitated by specific assessment scales, such as the Canine Dementia Scale (CADES). Therapeutic approaches encompass both pharmacological treatments, like selegiline and antioxidants, and non-pharmacological interventions, such as environmental enrichment and cognitive stimulation. This study aims to review existing literature on CCDS, exploring the syndrome’s etiological, diagnostic, and therapeutic aspects. The methodology included a systematic search of scientific articles in the PubMed, Google Scholar, and Scopus databases using terms related to CCDS and neurodegeneration. Clinical and comparative studies with Alzheimer’s Disease in humans were reviewed. Findings suggest that innovative interventions, such as photobiomodulation and stem cell therapies, show promise but require further validation.